Mr & Mrs God In The Creation Kitchen - Nancy Wood (Massachusetts, United States Candlewick Press,U.S., 2006)
What will this cosmic couple cook up next? Nancy Wood's lively take on how a duo of married chefs got all of us started is magically and hilariously brought to life through Timothy Basil Ering's extraordinary illustrations. Deep in the heavens, in the space between the clouds, Mr. and Mrs. God are hard at work in their Creation Kitchen. They've got frying pans and mixing bowls, beaters and whisks, and an oven big enough to roast a star - which is just what they are doing! After the sun and earth are finished, all kinds of interesting creations come next, with beaks and claws and growls and roars baked right in. When each creature is cooked to perfection, they set it down on Earth. But that's only the beginning. . . .
Keywords: Circle Time + Creation myths; Awe & Wonder -- Awe & Wonder